2004
DOI: 10.3390/ijerph2004020074
|View full text |Cite
|
Sign up to set email alerts
|

Association of Clinical Complications with Nutritional Status and the Prevalence of Leukopenia among Arsenic Patients in Bangladesh

Abstract: This study conducted in Bangladesh reports the relationship of clinical complications with nutritional status and the prevalence of leukopenia among arsenic exposed patients living in the rural villages. A total of 115 exposed individuals diagnosed as arsenicosis patients were randomly selected from four known arsenic endemic villages, and age-matched 120 unexposed subjects were enrolled in the study program. The duration of arsenic exposure in about 37% of the patients was at least 10 yrs, while the populatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
2

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 27 publications
1
18
2
Order By: Relevance
“…Average UAs concentration of the present study was higher than the other studies, such as 16 to 2746 μg/g [37] and smaller than 11 to 4144 μg/g [38]. The other study reported that the mean arsenic concentrations in the drinking water for the exposed and unexposed (control) population were 218.1 μg/L and 11.3 μg/L, respectively [39]. …”
Section: E Assessment Of Arsenic Concentration In Urine Samplecontrasting
confidence: 48%
“…Average UAs concentration of the present study was higher than the other studies, such as 16 to 2746 μg/g [37] and smaller than 11 to 4144 μg/g [38]. The other study reported that the mean arsenic concentrations in the drinking water for the exposed and unexposed (control) population were 218.1 μg/L and 11.3 μg/L, respectively [39]. …”
Section: E Assessment Of Arsenic Concentration In Urine Samplecontrasting
confidence: 48%
“…Also increased mortality from ischemic heart disease has been reported among copper smelter workers exposed to arsenic [11]. Our recent publication reports an association of clinical complications of arsenic toxicity with the nutritional status of the intoxicated subjects [12]. Study carried out in Taiwan concluded that patients affected with black foot disease, a unique peripheral vascular disease caused by long-term arsenic exposure via drinking water, have a significantly higher mortality due to ischemic heart disease [13].…”
Section: Introductionmentioning
confidence: 99%
“…Melanosis is found on trunk and gradually covers the whole body. [1][2][3] Some signs are also seen in other tissues of the body like tongue, gingival and buccal mucosa. 2 Arsenic was once used topically as pulp devitalizer for endodontic treatment.…”
Section: Introductionmentioning
confidence: 94%
“…[1][2][3] Some signs are also seen in other tissues of the body like tongue, gingival and buccal mucosa. 2 Arsenic was once used topically as pulp devitalizer for endodontic treatment. Arsenic is toxic to vital pulp due to prolonged leakage of arsenic trioxide that can cause severe damage to periodontal tissues and also can widespread necrosis of gingiva and bone, which can lead to osteomyelitis of the jaws.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation